The Influence of Competence and Work Discipline on the Performance of Government Employees - Malik, Sahruddin; Luthfi, Mochtar; Malik, Muh. Tahir; Amelia (Journal of Indonesian Scholars for Social Research, 2023)
This study examines the effect of competence and work discipline on employee performance at the Inspectorate Office of Maros Regency. The sample for this research was 80 employees who were randomly selected using a random sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The study results a show that competence and work discipline positively and significantly impact employee performance. This shows that increasing competence and work discipline can improve employee performance. In addition, further research can be carried out using a larger sample and examining other factors that can affect employee performance. This research implies that the management must pay more attention to competency development and improving employee work discipline. The recommendation from this research is that the administration must provide training, education, and skill development to employees to improve competence, as well as provide appropriate supervision, sanctions, and rewards for employees who are not/disciplined.